Assessment of dental caries and salivary nitric oxide levels in children with dyspepsia - ALTURFAN, EBRU IŞIK; AKYÜZ, SERAP HATİCE (BMC, 2019)
Background: The increase in nitric oxide (NO) levels in the oral cavity and saliva have been associated with various oral diseases; however, the gastro-salivary interaction of NO remains controversial. Thus, the aim of this study was to determine and compare salivary NO levels of dyspeptic and non-dyspeptic healthy children and to conduct an evaluation of its association with dental caries. Methods: Seventy children with dyspepsia (dyspeptic group) and 30 children without any gastrointestinal complaints (control group) were included in the study. Two biopsies from the gastric tissues were collected from dyspeptic children for histopathologic examination. Oral examination involved the assessment of dental caries, gingival index, plaque index, buffering capacity, salivary flow rate and pH. Salivary Streptococcus mutans (S. mutans) and Lactobacilli sp. counts were performed by commercial kits. For the comparison of the normal distribution between dyspeptic and control groups, Student t-test and for the comparison of the non-normal distribution, Kruskal-Wallis and Mann-Whitney-U tests were used. Chi-square test was used for comparison of qualitative data and the Pearson correlation test was used to evaluate the association between certain variables. Significance was assessed at p<0.05 level. Results: Helicobacter pylori (H.pylori) were found in gastric biopsies of 84.2% (59/70) of the dyspeptic children. While the mean salivary NO values did not differ significantly between gastric H.pylori positive, negative and control groups, the salivary NO level of the dyspeptic group (213.7 +/- 51.68 mu mol/dL) was found to be significantly higher than the control group (185.7 +/- 16.66 mu mol/dL). No significant relationship was found between the mean salivary NO values, DMFT/dmft numbers and other oral parameters. Conclusions: The association of dental caries and salivary NO levels could not be considered specific in the current study. Although there were no statistically significant differences between salivary NO levels of gastric H.pylori positive, gastric H.pylori negative and control groups, greater salivary NO levels among dyspeptic children compared with the control group demonstrated that the concentration of NO in the saliva could be used as a biological marker in dyspepsia, which could lead to the improvement of more specified, uncomplicated and susceptible methods for analysis.
Keywords: Nitric oxide; Saliva; Dental caries; Dyspepsia; Gastric diseases; NITRATE; EXPERIENCE; RISK